2014
DOI: 10.3832/ifor0644-007
|View full text |Cite
|
Sign up to set email alerts
|

Amount and distribution of coarse woody debris in pine ecosystems of north-western Spain, Russia and the United States

Abstract: © iForest -Biogeosciences and Forestry IntroductionCoarse woody debris (CWD) is one of the most important functional and structural components of forest ecosystems (Harmon et al. 1986, McComn & Lindenmayer 1999. CWD affects nutrient cycling, carbon storage and hydrological processes. It also serves as an essential substrate for a multitude of species, including numerous rare and endangered species (von Oheimb et al. 2007).Numerous studies have examined the role of CWD in maintaining biodiversity (Esseen et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…However, the amount of CWD was less than 12.56 Mg ha −1 in a 55-65-year-old secondary natural forest of Chinese red pine (P. tabulaeformis) [46]. In addition, the 5.7% of the CWD ratio (ratio of dead to live wood mass) was relatively small compared to the range from 2.8% to 126.6% in other pine ecosystems, including stands disturbed by fire or insect damage [12]. In regard to the contribution of CWD to N input in this study site, annual N input from CWD caused by annual tree mortality comprised approximately 11.1% of total N stock in CWD, and comprised less than 3.5% of 65.65 kg N ha −1 year −1 from total fine litterfall, indicating less contribution of CWD to N cycles than fine litter.…”
Section: And N Contents Of Cwdmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the amount of CWD was less than 12.56 Mg ha −1 in a 55-65-year-old secondary natural forest of Chinese red pine (P. tabulaeformis) [46]. In addition, the 5.7% of the CWD ratio (ratio of dead to live wood mass) was relatively small compared to the range from 2.8% to 126.6% in other pine ecosystems, including stands disturbed by fire or insect damage [12]. In regard to the contribution of CWD to N input in this study site, annual N input from CWD caused by annual tree mortality comprised approximately 11.1% of total N stock in CWD, and comprised less than 3.5% of 65.65 kg N ha −1 year −1 from total fine litterfall, indicating less contribution of CWD to N cycles than fine litter.…”
Section: And N Contents Of Cwdmentioning
confidence: 91%
“…Global CWD contains approximately 36-72 Pg C, which may affect the total global forest C stock [10,11]. The CWD quantity and distribution is influenced by tree mortality and decomposition rate, which vary with climate, site characteristics, tree species, age, and disturbance dynamics [1][2][3][4][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Tree mortality contributes to coarse woody debris (CWD), a key carbon reservoir in mature and old-growth forests. Differences in CWD stocks have been found among forest types (Herrero et al, 2010 and2014a). The decomposition rates of dead woody materials varies with the species, size, type of material (i.e., bark, sapwood or heartwood), and site conditions (i.e., temperature, humidity, etc.).…”
Section: Rotation Lengthmentioning
confidence: 99%
“…However, protocols for dead wood assessment differ among European NFIs, and data are difficult to compare (Herrero et al 2013). Schuck et al (2004) analysed inventory methods for 22 countries and found differences among attributes measured, diameter thresholds and sampling design.…”
Section: Communicated By: Enrico Marchimentioning
confidence: 99%